2014
DOI: 10.1097/mib.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Crohnʼs Disease from Intestinal Tuberculosis by Clinical and CT Enterographic Models

Abstract: The accuracy of CT enterographic model suggests the possibility of using CT enterography as an alternative to endoscopy in the differentiation between CD and ITB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 29 publications
4
70
1
1
Order By: Relevance
“…The median duration in CD (6–53.3 months, range 0.3–300 months) was significantly greater than that in ITB (3–23.4 months, range 0–120 months) in five of the studies (1,6,1214,16,30). In the other studies, the reported mean duration of symptoms in meta-analysis was 26.5 months (95% CI=15.7–37.3) longer for CD compared with that for ITB (2,11,15,31–34). Although the studies reporting means had a very high heterogeneity with I 2 of 97.7%, all of the studies showed a longer duration in CD (Supplementary Figures online).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The median duration in CD (6–53.3 months, range 0.3–300 months) was significantly greater than that in ITB (3–23.4 months, range 0–120 months) in five of the studies (1,6,1214,16,30). In the other studies, the reported mean duration of symptoms in meta-analysis was 26.5 months (95% CI=15.7–37.3) longer for CD compared with that for ITB (2,11,15,31–34). Although the studies reporting means had a very high heterogeneity with I 2 of 97.7%, all of the studies showed a longer duration in CD (Supplementary Figures online).…”
Section: Resultsmentioning
confidence: 88%
“…ESR was reported in continuous values in six studies (four for mean and two for median) (1,11,12,15,17,34) and in dichotomous results (normal vs. abnormal value) in four studies (2,33,35,36). Meta-analyses were performed separately.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This model had high specificity and positive predictive value; however, the sensitivity was relatively low because of the low frequency of individual features in either disease. Numerous recent studies have also evaluated the role of CT in differentiating between CD and ITB 2021222324. Therefore, we tried to collate the results of all these studies to evaluate the overall role of CT in differentiating between CD and ITB.…”
Section: Introductionmentioning
confidence: 99%